2001
DOI: 10.1080/080394801317080846
|View full text |Cite
|
Sign up to set email alerts
|

Parent-reported competence and emotional and behavioral problems in Finnish adolescents

Abstract: This study was part of an 8-year follow-up study of the Epidemiological Multicenter Child Psychiatric Study in Finland. The Child Behavior Checklists (CBCLs) were analyzed for 598 15- to 16-year-old adolescents living in the southwestern area of Finland in 1997. The internal consistency of the CBCL syndrome scales was adequate (the alpha coefficient ranged from 0.66 to 0.89). The CBCL scores differentiated between non-referred adolescents and adolescents who had been referred to the mental health service or ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…These findings replicated in an Asian society results previously reported in the US [3,9] and in various European societies [10][11][12][13][14]. However, unlike Western findings, the TRF generally had larger referral status effects, ORs, and percentage of referred children with deviant scores than the CBCL.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings replicated in an Asian society results previously reported in the US [3,9] and in various European societies [10][11][12][13][14]. However, unlike Western findings, the TRF generally had larger referral status effects, ORs, and percentage of referred children with deviant scores than the CBCL.…”
Section: Discussionsupporting
confidence: 84%
“…Achenbach and Rescorla [3,9] reported that scores on syndrome scales, DSM-oriented scales, Internalizing, Externalizing, and Total problems were significantly higher for clinically referred children than for demographically matched non-referred children, after controlling for age, gender, SES, and ethnicity in US samples averaging 2,500 children. Similar findings have been found in European societies such as Denmark [10], Finland [11], Germany [12], and the Netherlands [13,14].…”
Section: Introductionsupporting
confidence: 82%
“…The mean age of the adolescents was 16.0 years (standard deviation (s), 0.5) (12, 16 -19). The differences between responders and non-responders have been described in our previous paper (12). A somewhat higher percentage of non-responders had scored above the cut-off points in screening instruments at age 8 years than responders.…”
Section: Study Sample and Designsupporting
confidence: 62%
“…Previously, we have reported data on psychometric properties of the CBCL Parent Rating Form, on the basis of same sample of Finnish adolescents (12).…”
mentioning
confidence: 99%
“…Internalizing behaviors were measured with two indexes Child Depression (11 items), and Child Withdrawal (9 items), which were created by summing the items. This rating scale has been used widely with various ethnic groups in the U.S. and in other countries (e.g., Germany, Finland) and has been found to have adequate validity and reliability (Helstelae, Sourander, & Bergroth, 2001). Sample items for internalizing problem behaviors include "I am shy or timid," and for externalizing problem behaviors include "I am disobedient at school."…”
Section: Methodsmentioning
confidence: 99%